UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE RECIPROCAL LEARNING PADA SISWA KELAS X.8 SMAN 1 LEMBAH MELINTANG - nilda nilda (STKIP Pesisir Selatan, 2017)
Based on the results of student learning x.8 Class SMAN 1 Valley Crossing in Mathematics sub Perform algebraic manipulation in the engineering calculations relating to comparisons, functions, equations and trigonometric identities found that results for students in the subjects of Mathematics sub Perform algebraic manipulation in the calculation related technical comparison, functions, equations and trigonometric identities are still very low. The average student learning outcomes are still under KKM. The purpose of this study is to describe and obtain information about the efforts to improve student learning outcomes in mathematics sub Perform algebraic manipulation in the engineering calculations relating to comparisons, functions, equations and trigonometric identities through Cooperative Learning Model in the Classroom Learning Reciprocal x.8 SMAN 1 Valley Crossing West Pasaman.This research is a class act. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subject of the study consisted of 30 students Grades x.8 SMAN 1 Valley Crossing. Data were collected by using observation sheet and daily tests. Data were analyzed using percentages.Based on the results of research and discussion that has been raised, it can be concluded that the Model Cooperative Learning Reciprocal Learning can improve student learning outcomes in mathematics sub Perform algebraic manipulation in the engineering calculations relating to comparisons, functions, equations and trigonometric identities in SD N 09 Pasaman. Learning outcomes of students from the first cycle to the second cycle. The results of students in the first cycle was 54.02 (Enough) increased to 84.62 (good) with an increase of 30.60%.